Heat stroke patients managed in intensive care unit: a case series - Koirala, Eliza; Gauli, Basanta; Maharajan, Rabin (Journal of Chitwan Medical College, 2024)
Heat stroke is an environmental disease and potentially fatal. It commonly mimics sepsis with shock. We report the cases of patients who developed a severe non-exertional heatstroke with consecutive multiple organ dysfunction. There were different categories of patients with a different course of illness and outcomes. We present a case series of five patients with heat strokes and altered levels of consciousness, highly elevated temperatures, and needing intensive care at our hospital. Most patients were elderly, one had Down’s syndrome. All cases had features mimicking sepsis. Patients were treated in the medical intensive care unit (MICU). Low procalcitonin with a negative tropical infection panel made us highly think of heat stroke as a diagnosis.